Polymerizable liquid crystal composition, polarizing film and method for producing the same, polarizing plate and display device

JP7640623B2Active Publication Date: 2025-03-05SUMITOMO CHEM CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023113448
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-02-01
Filing Date
2023-07-11
Publication Date
2025-03-05
Estimated Expiration
2039-01-22

AI Technical Summary

Benefits of technology

【0007】 本発明によれば、太陽光に曝された場合の二色性色素の変性に対する高い抑制効果を有し、経時的な偏光性能の低下を抑制し得る偏光膜を形成するのに適した重合性液晶組成物を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007640623000001
    Figure 0007640623000001
  • Figure 0007640623000002
    Figure 0007640623000002
  • Figure 0007640623000003
    Figure 0007640623000003
Patent Text Reader

Abstract

To provide a polymerizable liquid crystal composition suitable for forming a polarizing film (polarizer) that has a high suppression effect on modification of a dichroic dye when exposed to sun rays and that can suppress decrease in the polarization performance with time.SOLUTION: The polymerizable liquid crystal composition comprises a polymerizable liquid crystal compound having at least one polymerizable group and exhibiting smectic liquid crystallinity, a dichroic dye, and an antioxidant, in which the polymerizable group of the polymerizable liquid crystal compound is a radically polymerizable group, and the antioxidant satisfies an expression (1): 0.8°C≤T1-T2 in relation to the polymerizable liquid crystal compound. In expression (1), T1 is a phase transition temperature of the polymerizable liquid crystal compound to a liquid crystal phase that develops on the lowest temperature side when, after the polymerizable liquid crystal compound is heated in air to 130°C, the phase transition temperature is measured while cooling the compound at a rate of 5°C / min down to 23°C; and T2 is a phase transition temperature of a mixture comprising 100 pts.mass of the polymerizable liquid crystal compound and 1 pt.mass of the antioxidant to a liquid crystal phase that develops on the lowest temperature side when, after the mixture is heated in air to 130°C, the phase transition temperature is measured while cooling the mixture at a rate of 5°C / min down to 23°C.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polymerizable liquid crystal composition, a polarizing film and a method for producing the same, and a polarizing plate and a display device including the same. [Background technology]

[0002] Conventionally, polarizing plates are used by being attached to image display elements such as liquid crystal cells or organic EL display elements in various image display panels such as liquid crystal display panels and organic electroluminescence (organic EL) display panels. As such a polarizing plate, a polarizing plate having a configuration in which a protective layer such as a triacetyl cellulose film is laminated via an adhesive layer on at least one surface of a polarizer in which a compound exhibiting dichroism such as iodine or a dichroic dye is adsorbed and aligned on a polyvinyl alcohol-based resin film is known.

[0003] In recent years, there has been a continuous demand for thinner displays such as image display panels, and further thinner polarizing plates and polarizers, which are one of the components of such displays, are also being demanded. In response to such demands, for example, a thin host-guest type polarizer made of a polymerizable liquid crystal compound and a compound exhibiting dichroism has been proposed (Patent Documents 1 and 2). [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Special Publication No. 2007-510946 [Patent Document 2] JP 2013-37353 A Summary of the Invention [Problem to be solved by the invention]

[0005] Furthermore, in recent years, displays have come to be used in a variety of locations, including outdoors, and this has created a demand for the development of polarizers with excellent light resistance. Therefore, an object of the present invention is to provide a polymerizable liquid crystal composition suitable for forming a polarizing film (polarizer) that has a high inhibitory effect against the degeneration of a dichroic dye when exposed to sunlight and can inhibit deterioration of polarization performance over time. [Means for solving the problem]

[0006] The present inventors have conducted extensive research to solve the above problems and have completed the present invention. That is, the present invention provides the following preferred embodiments. [1] A polymerizable liquid crystal composition comprising a polymerizable liquid crystal compound having at least one polymerizable group and exhibiting smectic liquid crystal properties, a dichroic dye, and an antioxidant, The polymerizable group of the polymerizable liquid crystal compound is a radical polymerizable group, The antioxidant satisfies the formula (1) in relation to the polymerizable liquid crystal compound: 0.8℃ ≦ T1-T2 (1) (In the formula, T1 is the phase transition temperature to the liquid crystal phase which appears at the lowest temperature side when the phase transition temperature of the polymerizable liquid crystal compound is measured while heating the compound in the air to 130° C. and then cooling to 23° C. at a rate of 5° C. / min, and T2 is the phase transition temperature to the liquid crystal phase which appears at the lowest temperature side when the phase transition temperature of a mixture of 100 parts by mass of the polymerizable liquid crystal compound and 1 part by mass of the antioxidant is measured while heating the compound in the air to 130° C. and then cooling to 23° C. at a rate of 5° C. / min.) The polymerizable liquid crystal composition satisfies the above requirements. [2] The polymerizable liquid crystal composition according to [1] above, further comprising a solvent. [3] The polymerizable liquid crystal composition according to the above [1] or [2], wherein the dichroic dye is an azo dye. [4] The polymerizable liquid crystal composition according to any one of the above [1] to [3], wherein the polymerizable group of the polymerizable liquid crystal compound is an acryloyloxy group. [5] The polymerizable liquid crystal composition according to any one of [1] to [4] above, further comprising 0.1 to 15 parts by mass of an antioxidant relative to 100 parts by mass of the polymerizable liquid crystal composition. [6] The polymerizable liquid crystal composition according to any one of the above [1] to [5], wherein the antioxidant is at least one selected from the group consisting of a phenol-based compound, an alicyclic alcohol-based compound, and an amine-based compound. [7] The antioxidant is represented by the formula (2), (3) and (4): [ka] [In formulas (2) and (3), R1 to R5 are each independently -H, -OH, -NH2, a branched or unbranched alkyl group having 1 to 12 carbon atoms, or a branched or unbranched alkoxy group having 1 to 12 carbon atoms, and at least one of R1 to R5 in formulas (2) and (3) is -OH or -NH2.] The polymerizable liquid crystal composition according to any one of the above [1] to [6], having any structure represented by the following formula: [8] The antioxidant is represented by the formula (5): A1-L1-(A2-L2) n -A3(5) [In the formula, L1 and L2 each independently represent a single bond or a divalent linking group; A1 is represented by formula (2), (3) or (4): [ka] [In the formulas (2) and (3), R1 to R5 are defined as in [7] above] is a group represented by A2 is represented by the formula (6) or (7): [ka] [In formulas (6) and (7), R6 to R9 are each independently -H, -OH, -NH2, a branched or unbranched alkyl group having 1 to 12 carbon atoms, or a branched or unbranched alkoxy group having 1 to 12 carbon atoms] is a group represented by A3 is represented by the formula (8) or (9): [ka] [In formulas (8) and (9), R 10 ~R 14 are each independently -H, -OH, -NH2, a branched or unbranched alkyl group having 1 to 12 carbon atoms, or a branched or unbranched alkoxy group having 1 to 12 carbon atoms. wherein n is an integer of 0 to 2, and when n is 2, two A2's may be the same or different. The polymerizable liquid crystal composition according to the above [7], wherein the compound is represented by the formula: [9] A polarizing film which is a cured product of a polymerizable liquid crystal composition containing a dichroic dye, a polymerizable liquid crystal compound, and an antioxidant, The polarizing film exhibits a Bragg peak in an X-ray diffraction measurement, The antioxidant satisfies the formula (1) in relation to the polymerizable liquid crystal compound: 0.8℃ ≦ T1-T2 (1) (In the formula, T1 is the phase transition temperature to the liquid crystal phase which appears at the lowest temperature side when the phase transition temperature of the polymerizable liquid crystal compound is measured while heating the compound in the air to 130° C. and then cooling to 23° C. at a rate of 5° C. / min, and T2 is the phase transition temperature to the liquid crystal phase which appears at the lowest temperature side when the phase transition temperature of a mixture of 100 parts by mass of the polymerizable liquid crystal compound and 1 part by mass of the antioxidant is measured while heating the compound in the air to 130° C. and then cooling to 23° C. at a rate of 5° C. / min.) Meet the polarizing film.

[10] A polarizing plate comprising the polarizing film according to [9] above and a retardation film.

[11] The retardation film has the formula (X): 100 ≦ Re(550) ≦ 180 (X) (wherein Re(550) represents an in-plane retardation value at a wavelength of 550 nm) and an angle between a slow axis of the retardation film and an absorption axis of the polarizing film is substantially 45°.

[12] The retardation film has the formula (Y): Re(450) / Re(550) < 1 (Y) (In the formula, Re(450) and Re(550) represent in-plane retardation values ​​at wavelengths of 450 nm and 550 nm, respectively.) The polarizing plate according to

[10] or

[11] above, which satisfies the above condition.

[13] The polarizing plate according to any one of the above

[10] to

[12] , wherein the retardation film is composed of a polymer of a polymerizable liquid crystal compound in an aligned state.

[14] A display device comprising the polarizing film according to the above [9] or the polarizing plate according to any one of the above

[10] to

[13] .

[15] Forming a coating film of the polymerizable liquid crystal composition according to any one of [1] to [8] above. removing the solvent from the coating; raising the temperature to a temperature at which the polymerizable liquid crystal compound undergoes a phase transition to a liquid phase or higher, and then lowering the temperature to cause the polymerizable liquid crystal compound to undergo a phase transition to a smectic phase; and The polymerizable liquid crystal compound is polymerized while maintaining the smectic phase. A method for producing a polarizing film, comprising the steps of: Effect of the Invention

[0007] According to the present invention, it is possible to provide a polymerizable liquid crystal composition suitable for forming a polarizing film that has a high inhibitory effect against the degeneration of a dichroic dye when exposed to sunlight and can inhibit deterioration of the polarization performance over time. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, the embodiments of the present invention will be described in detail. Note that the scope of the present invention is not limited to the embodiments described here, and various modifications can be made without departing from the spirit of the present invention.

[0009] <Polymerizable liquid crystal composition> The polymerizable liquid crystal composition of the present invention contains a polymerizable liquid crystal compound (hereinafter, also referred to as "polymerizable liquid crystal compound (A)") having at least one polymerizable group and exhibiting smectic liquid crystal properties. By using a polymerizable liquid crystal compound exhibiting smectic liquid crystal properties, a polarizing film having a high degree of alignment order can be formed. The liquid crystal state exhibited by the polymerizable liquid crystal compound (A) is a smectic phase (smectic liquid crystal state), and from the viewpoint of realizing a higher degree of alignment order, a high-order smectic phase (high-order smectic liquid crystal state) is more preferable. Here, the high-order smectic phase means a smectic B phase, a smectic D phase, a smectic E phase, a smectic F phase, a smectic G phase, a smectic H phase, a smectic I phase, a smectic J phase, a smectic K phase, and a smectic L phase, and among these, a smectic B phase, a smectic F phase, and a smectic I phase are more preferable. The liquid crystal property may be either thermotropic or lyotropic, but thermotropic liquid crystal is preferred in terms of enabling precise control of the film thickness. The polymerizable liquid crystal compound may be a monomer, or may be an oligomer or polymer in which a polymerizable group is polymerized.

[0010] The polymerizable liquid crystal compound (A) is a liquid crystal compound having at least one polymerizable group. Here, the polymerizable group refers to a group that can be involved in a polymerization reaction by an active radical or an acid generated from a polymerization initiator. Examples of the polymerizable group contained in the polymerizable liquid crystal compound (A) include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, an oxetanyl group, etc. Among them, a radically polymerizable group is preferable, an acryloyloxy group, a methacryloyloxy group, a vinyl group, and a vinyloxy group are more preferable, an acryloyloxy group and a methacryloyloxy group are even more preferable, and an acryloyloxy group is even more preferable.

[0011] The polymerizable liquid crystal compound (A) is not particularly limited as long as it has at least one polymerizable group and exhibits smectic liquid crystal properties, and any known polymerizable liquid crystal compound can be used. Examples of the polymerizable liquid crystal compound (A) include a compound represented by formula (A1) and a polymer of the compound (hereinafter, the compound and the polymer may be collectively referred to as "polymerizable liquid crystal compound (A1)"). U 1 -V 1 -W 1 -X 1 -Y 1 -X 2 -Y 2 -X 3 -W 2 -V 2 -U 2 (A1) [In formula (A1), X 1 , X 2 and X 3 represent, independently of each other, a divalent aromatic group or a divalent alicyclic hydrocarbon group, in which a hydrogen atom contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom. 1 , X 2 and X 3 At least one of these is a 1,4-phenylene group which may have a substituent or a cyclohexane-1,4-diyl group which may have a substituent. Y 1 and Y 2 are each independently a single bond or a divalent linking group. U 1 represents a hydrogen atom or a polymerizable group. U 2 represents a polymerizable group. W 1 and W 2 are each independently a single bond or a divalent linking group. V 1 and V 2 each independently represents an alkanediyl group having 1 to 20 carbon atoms which may have a substituent, and -CH2- constituting the alkanediyl group may be replaced by -O-, -CO-, -S- or NH-.]

[0012] In the polymerizable liquid crystal compound (A1), X 1 , X 2 and X 3 are each independently preferably an optionally substituted 1,4-phenylene group or an optionally substituted cyclohexane-1,4-diyl group; X 1 , X 2 and X 3 At least one of X is an optionally substituted 1,4-phenylene group or an optionally substituted cyclohexane-1,4-diyl group. 1 and X 3 is preferably a cyclohexane-1,4-diyl group which may have a substituent, and the cyclohexane-1,4-diyl group is more preferably a trans-cyclohexane-1,4-diyl group. Examples of the optional substituent of the 1,4-phenylene group which may have a substituent or the cyclohexane-1,4-diyl group which may have a substituent include an alkyl group having 1 to 4 carbon atoms such as a methyl group, an ethyl group, and a butyl group, a cyano group, and a halogen atom such as a chlorine atom or a fluorine atom. It is preferably unsubstituted. Also, Y 1 and Y 2 If X is the same structure, 1 , X 2 and X 3 It is preferable that at least one of X has a different structure. 1 , X 2 and X 3 When at least one of the above has a different structure, smectic liquid crystallinity tends to be easily exhibited.

[0013] Y 1 and Y 2are each independently -CH2CH2-, -CH2O-, -CH2CH2O-, -COO-, -OCOO-, a single bond, -N=N-, -CR a =CR b -, -C≡C-, -CR a =N- or -CO-NR a - is preferred. a and R b each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 1 is more preferably -CH2CH2-, -COO- or a single bond, and Y 2 More preferably, X is -CH2CH2- or CH2O-. 1 , X 2 and X 3 If all have the same structure, Y 1 and Y 2 It is preferable that Y have different structures. 1 and Y 2 When the structures are different from each other, smectic liquid crystallinity tends to be easily exhibited.

[0014] U 2 is a polymerizable group. 1 is a hydrogen atom or a polymerizable group, and is preferably a polymerizable group. 1 and U 2 Preferably, both are polymerizable groups, and preferably both are radically polymerizable groups. Examples of the polymerizable group include the same groups as those exemplified above as the polymerizable group contained in the polymerizable liquid crystal compound (A). 1 and a polymerizable group represented by U 2 The polymerizable groups represented by the following formula (I) may be different from each other, but are preferably the same type of group.

[0015] V 1 and V 2Examples of the alkanediyl group represented by the formula (I) include a methylene group, an ethylene group, a propane-1,3-diyl group, a butane-1,3-diyl group, a butane-1,4-diyl group, a pentane-1,5-diyl group, a hexane-1,6-diyl group, a heptane-1,7-diyl group, an octane-1,8-diyl group, a decane-1,10-diyl group, a tetradecane-1,14-diyl group, and an icosane-1,20-diyl group. 1 and V 2 is preferably an alkanediyl group having 2 to 12 carbon atoms, and more preferably an alkanediyl group having 6 to 12 carbon atoms.

[0016] Examples of the substituent that the alkanediyl group may have include a cyano group and a halogen atom. The alkanediyl group is preferably unsubstituted, and more preferably an unsubstituted linear alkanediyl group.

[0017] W 1 and W 2 are each independently preferably a single bond, -O-, -S-, -COO- or -OCOO-, and more preferably a single bond or -O-.

[0018] Examples of the polymerizable liquid crystal compound (A1) include compounds represented by formulae (A-1) to (A-25). When the polymerizable liquid crystal compound (A1) has a cyclohexane-1,4-diyl group, the cyclohexane-1,4-diyl group is preferably a trans isomer.

[0019] [ka]

[0020] [ka]

[0021] [ka]

[0022] [ka]

[0023] [ka]

[0024] Among these, at least one selected from the group consisting of compounds represented by formula (A-2), formula (A-3), formula (A-4), formula (A-5), formula (A-6), formula (A-7), formula (A-8), formula (A-13), formula (A-14), formula (A-15), formula (A-16) and formula (A-17) is preferred. As the polymerizable liquid crystal compound (A1), one type may be used alone, or two or more types may be used in combination.

[0025] The polymerizable liquid crystal compound (A1) can be produced by a known method such as that described in Lub et al., Recl. Trav. Chim. Pays-Bas, 115, 321-328 (1996) or Japanese Patent No. 4,719,156.

[0026] The polymerizable liquid crystal composition of the present invention may contain a polymerizable liquid crystal compound other than the polymerizable liquid crystal compound (A) as long as the effect of the present invention is not impaired. From the viewpoint of obtaining a polarizing film having a high degree of alignment order, the ratio of the polymerizable liquid crystal compound (A) to the total mass of all the polymerizable liquid crystal compounds in the polymerizable liquid crystal composition is preferably 51% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more.

[0027] When the polymerizable liquid crystal composition of the present invention contains two or more polymerizable liquid crystal compounds (A), at least one of them may be the polymerizable liquid crystal compound (A1), or all of them may be the polymerizable liquid crystal compound (A1). By combining a plurality of polymerizable liquid crystal compounds, liquid crystallinity may be temporarily maintained even at a temperature below the liquid crystal-crystal phase transition temperature.

[0028] The content of the polymerizable liquid crystal compound in the polymerizable liquid crystal composition of the present invention is preferably 40 to 99.9 mass %, more preferably 60 to 99 mass %, and further preferably 70 to 99 mass %, based on the solid content of the polymerizable liquid crystal composition. When the content of the polymerizable liquid crystal compound is within the above range, the alignment property of the polymerizable liquid crystal compound tends to be high. In this specification, the solid content refers to the total amount of components excluding the solvent from the polymerizable liquid crystal composition.

[0029] The polymerizable liquid crystal composition of the present invention contains a dichroic dye. Here, the dichroic dye means a dye having different absorbance in the long axis direction of the molecule and absorbance in the short axis direction. The dichroic dye that can be used in the present invention is not particularly limited as long as it has the above-mentioned properties, and may be a dye or a pigment. Two or more types of dyes or pigments may be used in combination, or a dye and a pigment may be used in combination.

[0030] Dichroic dyes have a maximum absorption wavelength (λ MAX ) is preferable. Examples of such dichroic dyes include acridine dyes, oxazine dyes, cyanine dyes, naphthalene dyes, azo dyes, and anthraquinone dyes.

[0031] Examples of azo dyes include monoazo dyes, bisazo dyes, trisazo dyes, tetrakisazo dyes, and stilbene azo dyes. Bisazo dyes and trisazo dyes are preferred, and examples thereof include a compound represented by formula (I) (hereinafter also referred to as "compound (I)"). K 1 -(-N=NK 2 ) p -N=NK 3 (I) [In formula (I), K 1 and K. 3 each independently represents a phenyl group which may have a substituent, a naphthyl group which may have a substituent, or a monovalent heterocyclic group which may have a substituent. 2represents a p-phenylene group which may have a substituent, a naphthalene-1,4-diyl group which may have a substituent, or a divalent heterocyclic group which may have a substituent. p represents an integer of 1 to 4. When p is an integer of 2 or more, a plurality of K 2 may be the same or different. The -N=N- bond may be replaced with a -C=C-, -COO-, -NHCO-, or -N=CH- bond as long as the compound exhibits absorption in the visible region.

[0032] Examples of the monovalent heterocyclic group include groups in which one hydrogen atom has been removed from a heterocyclic compound such as quinoline, thiazole, benzothiazole, thienothiazole, imidazole, benzimidazole, oxazole, benzoxazole, etc. Examples of the divalent heterocyclic group include groups in which two hydrogen atoms have been removed from the above-mentioned heterocyclic compounds.

[0033] K 1 and K. 3 Phenyl, naphthyl and monovalent heterocyclic groups in 2 Examples of the substituent that the p-phenylene group, naphthalene-1,4-diyl group, and divalent heterocyclic group in the formula (I) may optionally have include an alkyl group having 1 to 4 carbon atoms; an alkoxy group having 1 to 4 carbon atoms, such as a methoxy group, an ethoxy group, and a butoxy group; a fluorinated alkyl group having 1 to 4 carbon atoms, such as a trifluoromethyl group; a cyano group; a nitro group; a halogen atom; and a substituted or unsubstituted amino group, such as an amino group, a diethylamino group, or a pyrrolidino group (a substituted amino group means an amino group having one or two alkyl groups having 1 to 6 carbon atoms, or an amino group in which two substituted alkyl groups are bonded to each other to form an alkanediyl group having 2 to 8 carbon atoms. An unsubstituted amino group is -NH2).

[0034] Among the compounds (I), the compounds represented by any one of formulas (I-1) to (I-6) are preferred. [ka] [In the formulas (I-1) to (I-8), B 1 ~B 30each independently represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, a nitro group, a substituted or unsubstituted amino group (the substituted amino group and the unsubstituted amino group are defined above), a chlorine atom, or a trifluoromethyl group. n1 to n4 each independently represent an integer of 0 to 3. If n1 is 2 or more, multiple B 2 may be the same or different, If n2 is 2 or more, multiple B 6 may be the same or different, If n3 is 2 or more, multiple B 9 may be the same or different, If n4 is 2 or more, multiple B 14 may be the same or different.]

[0035] The anthraquinone dye is preferably a compound represented by formula (I-9). [ka] [In formula (I-9), R 1 ~R 8 are each independently a hydrogen atom, -R x , -NH2, -NHR x , -NR x 2, -SR x Or a halogen atom. R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.

[0036] The oxazone dye is preferably a compound represented by formula (I-10). [ka] [In formula (I-8), R 9 ~R 15 are each independently a hydrogen atom, -R x , -NH2, -NHR x, -NR x 2, -SR x Or a halogen atom. R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms.

[0037] The acridine dye is preferably a compound represented by formula (I-11). [ka] [In formula (I-11), R 16 ~R 23 are each independently a hydrogen atom, -R x , -NH2, -NHR x , -NR x 2, -SR x Or a halogen atom. R x represents an alkyl group having 1 to 4 carbon atoms or an aryl group having 6 to 12 carbon atoms. In formula (I-9), formula (I-10) and formula (I-11), R x Examples of the alkyl group having 1 to 6 carbon atoms include a methyl group, an ethyl group, a propyl group, a butyl group, a pentyl group, and a hexyl group, and examples of the aryl group having 6 to 12 carbon atoms include a phenyl group, a toluyl group, a xylyl group, and a naphthyl group.

[0038] As the cyanine dye, the compounds represented by formula (I-12) and formula (I-13) are preferred. [ka] [In formula (I-12), D 1 and D. 2 represent, independently of each other, a group represented by any one of formulae (I-12a) to (I-12d). [ka] n5 represents an integer from 1 to 3. [ka] [In formula (I-13), D 3 and D. 4 each independently represents a group represented by any one of formulas (I-13a) to (1-13h). [ka] n6 represents an integer from 1 to 3.

[0039] The polymerizable liquid crystal composition of the present invention is excellent in suppressing photodegradation of the dichroic dye in the polarizing film when the polarizing film is formed, and therefore the effect of the present invention can be particularly pronounced when a dichroic dye that is weak against light such as ultraviolet light in sunlight and prone to photodegradation is used. Therefore, the polymerizable liquid crystal composition of the present invention is particularly advantageous when a dichroic dye that is prone to photodegradation is used. The dichroic dye contained in the polymerizable liquid crystal composition of the present invention is preferably an azo dye.

[0040] The content of the dichroic dye in the polymerizable liquid crystal composition of the present invention can be appropriately determined depending on the type of the dichroic dye used, and is preferably 0.1 to 50 parts by mass, more preferably 0.1 to 20 parts by mass, and even more preferably 0.1 to 12 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the dichroic dye is within the above range, the orientation of the polymerizable liquid crystal compound is unlikely to be disturbed, and a polarizing film having a high degree of orientation order can be obtained.

[0041] The polymerizable liquid crystal composition of the present invention contains an antioxidant. In the polymerizable liquid crystal composition of the present invention, the antioxidant is represented by the formula (1) in relation to the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition: 0.8℃ ≦ T1-T2 (1) Meet the following.

[0042] In formula (1), T1 is the phase transition temperature to a liquid crystal phase that occurs at the lowest temperature side when the phase transition temperature of the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition is measured while heating the compound to 130°C in air and then cooling the compound to 23°C at a rate of 5°C / min. T2 is the phase transition temperature to the liquid crystal phase that occurs at the lowest temperature side when a mixture consisting of 100 parts by mass of the polymerizable liquid crystal compound and 1 part by mass of the antioxidant is heated to 130°C in the air and then cooled to 23°C at a rate of 5°C / min while measuring the phase transition temperature. When the polymerizable liquid crystal composition of the present invention contains two or more polymerizable liquid crystal compounds, the above T1 and T2 are measured using a polymerizable liquid crystal compound (mixture) having the same composition as the polymerizable liquid crystal compound constituting the polymerizable liquid crystal composition. The detailed measurement method of T1 and T2 is as described in the examples described later.

[0043] In general, excellent polarization performance can be obtained when the polymerizable liquid crystal compound and the dichroic dye are aligned with a high degree of order. However, in such an alignment state, the dichroic dye is present in a state of being included in the polymerizable liquid crystal compound, and therefore, the alignment of the polymerizable liquid crystal compound is disturbed by the addition of an antioxidant, which may cause a problem of a decrease in polarization performance.

[0044] The polymerizable liquid crystal composition of the invention contains an antioxidant that satisfies the above formula (1), and thus can be highly effective in suppressing deterioration of the polarization performance when a polarizing film is formed. In formula (1), T1-T2 is an index that indicates the effect of the antioxidant on the phase transition temperature in the liquid crystal state. The larger the value of T1-T2, the more similar the molecular structure of the polymerizable liquid crystal compound and the antioxidant are, and the more they are present in a mixed state in the liquid crystal state, and the antioxidant is aligned together with the polymerizable liquid crystal compound. Therefore, it is presumed that the larger the value of T1-T2, the closer the intermolecular distance between the dichroic dye and the antioxidant that are present in a state of being encapsulated in the polymerizable liquid crystal compound, and the more effective it is in suppressing the photodegradation of the dichroic dye, and the less likely it is to disturb the alignment of the polymerizable liquid crystal compound, making it possible to obtain a polarizing film with a high degree of alignment order.

[0045] In the antioxidant contained in the polymerizable liquid crystal composition of the present invention, the above T1-T2 value is 0.8°C or more, preferably 0.9°C or more, more preferably 1.0°C or more, even more preferably 1.2°C or more, and particularly preferably 1.5°C or more. If the value of T1-T2 is less than 0.8°C, the molecular structure of the polymerizable liquid crystal compound and the molecular structure of the antioxidant are significantly different, making it difficult to orient the antioxidant together with the polymerizable liquid crystal compound with a high degree of order. As a result, it is difficult to fully exert the effect of suppressing photodegradation of the dichroic dye. On the other hand, if the value of T1-T2 is within the above range, the antioxidant can be arranged near the dichroic dye included in the polymerizable liquid crystal compound, and a high effect of suppressing the deterioration of the polarization performance can be expected. In the present invention, the upper limit of T1-T2 is not particularly limited, but is usually 35° C. or lower, preferably 30° C. or lower, and more preferably 25° C. or lower.

[0046] In the polymerizable liquid crystal composition, the antioxidant is not particularly limited as long as it satisfies the above formula (1) with the polymerizable liquid crystal compound and can exhibit the effects of the present invention, and known antioxidants can be used. From the viewpoint of having a high inhibitory effect against photodegradation of the dichroic dye, so-called primary antioxidants that have the effect of capturing radicals and preventing autoxidation are preferred. Therefore, it is more preferable that the antioxidant contained in the polymerizable liquid crystal composition of the present invention is at least one selected from the group consisting of phenol-based compounds, alicyclic alcohol-based compounds, and amine-based compounds. The antioxidant may be used alone or in combination of two or more types.

[0047] Examples of the antioxidant selected from the group consisting of phenolic compounds, alicyclic alcohol compounds, and amine compounds include compounds represented by the formulas (2), (3), and (4): [ka] Examples of the compound include compounds having any of the structures represented by the following formula:

[0048] In formulas (2) and (3), R1 to R5 are each independently -H, -OH, -NH2, a branched or unbranched alkyl group having 1 to 12 carbon atoms, or a branched or unbranched alkoxy group having 1 to 12 carbon atoms, and at least one of R1 to R5 in formulas (2) and (3) is -OH or -NH2.

[0049] Examples of the branched or unbranched alkyl group having 1 to 12 carbon atoms include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, a tert-butyl group, a pentyl group, a hexyl group, a 2-ethylhexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, and a dodecyl group.

[0050] Examples of the branched or unbranched alkoxy group having 1 to 12 carbon atoms include a methoxy group, an ethoxy group, a propoxy group, a butoxy group, a pentyloxy group, a hexyloxy group, an octyloxy group, a 2-ethylhexyloxy group, a nonyloxy group, a decyloxy group, an undecyloxy group, and a dodecyloxy group.

[0051] In formulas (2) and (3), it is preferable that -OH or -NH2 present in at least one of R1 to R5 is present in R1, and in this case, R2 to R5 are more preferably -H, a branched or unbranched alkyl group having 1 to 12 carbon atoms, or a branched or unbranched alkoxy group having 1 to 12 carbon atoms, and further preferably -H.

[0052] Examples of the antioxidant having a structure represented by the above formula (2), (3) or (4) include the antioxidant represented by the formula (5): A1-L1-(A2-L2) n -A3(5) Examples of the compound include those represented by the following formula:

[0053] In formula (5), L1 and L2 each independently represent a single bond or a divalent linking group.

[0054] A1 is a group represented by the above formula (2), (3) or (4).

[0055] A2 is represented by the formula (6) or (7): [ka] [In formulas (6) and (7), R6 to R9 are each independently -H, -OH, -NH2, a branched or unbranched alkyl group having 1 to 12 carbon atoms, or a branched or unbranched alkoxy group having 1 to 12 carbon atoms] It is a group represented by the following formula: A3 is represented by the formula (8) or (9): [ka] [In formulas (8) and (9), R 10 ~R 14 are each independently -H, -OH, -NH2, a branched or unbranched alkyl group having 1 to 12 carbon atoms, or a branched or unbranched alkoxy group having 1 to 12 carbon atoms. It is a group represented by the following formula: n is an integer of 0 to 2, and when n is 2, two A2's may be the same or different.

[0056] Examples of the divalent linking group in L1 and L2 include a single bond, an ether group, a carbonyl group, an ester group, an amide group, an azo group, etc. As L1 and L2, a bonding species that does not absorb visible light as an antioxidant is preferable, a single bond, an ether group, and an ester group are more preferable, and a single bond and an ether group are particularly preferable.

[0057] Examples of A1 include groups similar to the structures exemplified above as the structures represented by the above formulas (2), (3) and (4). A1 is preferably a group represented by formula (2) or (4), more preferably a group represented by formula (2). It is further preferable that R1 is -OH, and R2 to R5 are each independently -H or -CH3, and it is particularly preferable that R2 to R5 are all -H.

[0058] R6 to R in A2 and A3 14 Examples of the branched alkyl group having 1 to 12 carbon atoms, the unbranched alkyl group having 1 to 12 carbon atoms, the branched alkoxy group having 1 to 12 carbon atoms, and the unbranched alkoxy group having 1 to 12 carbon atoms, represented by the following formula (I), include the same groups as the branched alkyl group having 1 to 12 carbon atoms, the unbranched alkyl group having 1 to 12 carbon atoms, the branched alkoxy group having 1 to 12 carbon atoms, and the unbranched alkoxy group having 1 to 12 carbon atoms exemplified above as R1 to R5 in A1.

[0059] In A2, R6 to R9 are each preferably independently -H or -CH3, more preferably -H, still more preferably all of R6 to R9 are -H or -CH3, and particularly preferably all of R6 to R9 are -H.

[0060] In A3, R 12 is a branched or unbranched alkyl group having 1 to 12 carbon atoms, or a branched or unbranched alkoxy group having 1 to 12 carbon atoms, and R 10 , R 11 , R 13 and R 14 are each preferably independently -H or -CH; R 10 , R 11 , R 13 and R 14 It is particularly preferred that all of are -H.

[0061] The weight average molecular weight of the antioxidant is preferably 600 or less, more preferably 500 or less, and further preferably 450 or less. When the weight-average molecular weight of the antioxidant is 600 or less, the antioxidant can be arranged in the vicinity of the dichroic dye without significantly disturbing the alignment of the polymerizable liquid crystal compound, and therefore the effect of suppressing photodegradation of the dichroic dye can be further improved. Furthermore, when the weight-average molecular weight of the antioxidant is 400 or less, the antioxidant is less likely to have absorption in the visible light wavelength region, and the deterioration of the polarization performance can be more effectively suppressed, which is more preferable.

[0062] In the polymerizable liquid crystal composition of the present invention, examples of the antioxidant include the following compounds.

[0063] [ka]

[0064] Among them, antioxidants with small steric hindrance and high linearity as molecular structure are preferred because they tend to be easily aligned with the polymerizable liquid crystal compound and have excellent photodegradation suppression effect of the dichroic dye. The antioxidant in the polymerizable liquid crystal composition of the present invention is not limited thereto, but 4-n-octyloxyphenol, 4-n-decyloxyphenol, 4-n-dodecyloxyphenol, 4,4'-biphenol, 4-ethoxy-4'-hydroxybiphenyl, 4-butoxy-4'-hydroxybiphenyl, 4-octyloxy-4'-hydroxybiphenyl, 4-decyloxy-4'-hydroxybiphenyl, and 4-dodecyloxy-4'-hydroxybiphenyl are preferred.

[0065] The content of the antioxidant in the polymerizable liquid crystal composition of the present invention is preferably 0.1 to 15 parts by mass, more preferably 0.3 parts by mass or more, even more preferably 0.5 parts by mass or more, more preferably 12 parts by mass or less, even more preferably 8 parts by mass or less, and particularly preferably 4 parts by mass or less, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the antioxidant is equal to or more than the lower limit, the photodegradation of the dichroic dye can be effectively suppressed. When the content of the antioxidant is equal to or less than the upper limit, the alignment of the polymerizable liquid crystal compound is unlikely to be disturbed, and a high effect of suppressing the photodegradation of the dichroic dye can be expected.

[0066] The polymerizable liquid crystal composition of the present invention may contain a polymerization initiator. The polymerization initiator is a compound capable of initiating the polymerization reaction of the polymerizable liquid crystal compound, and a photopolymerization initiator is preferred because it can initiate the polymerization reaction under lower temperature conditions.Specific examples of the photopolymerization initiator include photopolymerization initiators capable of generating active radicals or acids under the action of light, and among these, photopolymerization initiators that generate radicals under the action of light are preferred.The polymerization initiators can be used alone or in combination of two or more kinds.

[0067] Examples of the polymerization initiator include a benzoin compound, a benzophenone compound, an alkylphenone compound, an acylphosphine oxide compound, a triazine compound, an iodonium salt, and a sulfonium salt.

[0068] Examples of the benzoin compound include benzoin, benzoin methyl ether, benzoin ethyl ether, benzoin isopropyl ether, and benzoin isobutyl ether.

[0069] Examples of the benzophenone compound include benzophenone, methyl o-benzoylbenzoate, 4-phenylbenzophenone, 4-benzoyl-4'-methyldiphenyl sulfide, 3,3',4,4'-tetra(tert-butylperoxycarbonyl)benzophenone, and 2,4,6-trimethylbenzophenone.

[0070] Examples of the alkylphenone compounds include diethoxyacetophenone, 2-methyl-2-morpholino-1-(4-methylthiophenyl)propan-1-one, 2-dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one, 2-hydroxy-2-methyl-1-phenylpropan-1-one, 1,2-diphenyl-2,2-dimethoxyethan-1-one, 2-hydroxy-2-methyl-1-[4-(2-hydroxyethoxy)phenyl]propan-1-one, 1-hydroxycyclohexyl phenyl ketone, and oligomers of 2-hydroxy-2-methyl-1-[4-(1-methylvinyl)phenyl]propan-1-one.

[0071] Examples of the acylphosphine oxide compound include 2,4,6-trimethylbenzoyldiphenylphosphine oxide and bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide.

[0072] The triazine compounds include 2,4-bis(trichloromethyl)-6-(4-methoxyphenyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxynaphthyl)-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-(4-methoxystyryl)-1,3,5-triazine, and 2,4-bis(trichloromethyl)-6-[2-(5-methylfuran-2-yl)ethenyl] 2,4-bis(trichloromethyl)-6-[2-(furan-2-yl)ethenyl]-1,3,5-triazine, 2,4-bis(trichloromethyl)-6-[2-(4-diethylamino-2-methylphenyl)ethenyl]-1,3,5-triazine and 2,4-bis(trichloromethyl)-6-[2-(3,4-dimethoxyphenyl)ethenyl]-1,3,5-triazine.

[0073] As the polymerization initiator, commercially available ones can be used. Examples of commercially available polymerization initiators include "Irgacure (registered trademark) 907", "Irgacure (registered trademark) 184", "Irgacure (registered trademark) 651", "Irgacure (registered trademark) 819", "Irgacure (registered trademark) 250", "Irgacure (registered trademark) 369" (Ciba Japan Co., Ltd.); "Seikuol (registered trademark) BZ", "Seikuol (registered trademark) Z", "Seikuol (registered trademark) 100", "Seikuol (registered trademark) 200", "Seikuol (registered trademark) 1 ... Examples of such compounds include "Kayacure (registered trademark) BEE" (Seiko Chemical Co., Ltd.); "Kayacure (registered trademark) BP100" (Nippon Kayaku Co., Ltd.); "Kayacure (registered trademark) UVI-6992" (Dow Chemicals); "ADEKA Optomer SP-152", "ADEKA Optomer SP-170" (ADEKA Corporation); "TAZ-A", "TAZ-PP" (Nippon SiberHegner AG); and "TAZ-104" (Sanwa Chemical Co., Ltd.).

[0074] When the polymerizable liquid crystal composition contains a polymerization initiator, the content of the polymerization initiator may be appropriately determined depending on the type and amount of the polymerizable liquid crystal compound contained in the polymerizable liquid crystal composition, and is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound. When the content of the polymerization initiator is within the above range, the polymerizable liquid crystal compound can be polymerized without disturbing the alignment.

[0075] When the polymerizable liquid crystal composition contains a photopolymerization initiator, it may further contain a photosensitizer. By using a photosensitizer, the polymerization reaction of the polymerizable liquid crystal compound can be further promoted. Examples of photosensitizers include xanthone compounds such as xanthone and thioxanthone (2,4-diethylthioxanthone, 2-isopropylthioxanthone, etc.), anthracene compounds such as anthracene and alkoxy group-containing anthracene (dibutoxyanthracene, etc.), phenothiazine, rubrene, etc. Photosensitizers can be used alone or in combination of two or more kinds.

[0076] The content of the photosensitizer in the polymerizable liquid crystal composition of the present invention may be appropriately determined depending on the types and amounts of the photopolymerization initiator and the polymerizable liquid crystal compound, and is preferably 0.1 to 30 parts by mass, more preferably 0.5 to 10 parts by mass, and even more preferably 0.5 to 8 parts by mass, relative to 100 parts by mass of the polymerizable liquid crystal compound.

[0077] The polymerizable liquid crystal composition of the present invention may contain a leveling agent. The leveling agent has a function of adjusting the fluidity of the polymerizable liquid crystal composition and making the coating film obtained by applying the polymerizable liquid crystal composition flatter, and specifically includes a surfactant. As the leveling agent, at least one selected from the group consisting of leveling agents mainly composed of a polyacrylate compound and leveling agents mainly composed of a fluorine atom-containing compound is preferable. The leveling agents can be used alone or in combination of two or more kinds.

[0078] Examples of leveling agents containing a polyacrylate compound as a main component include "BYK-350", "BYK-352", "BYK-353", "BYK-354", "BYK-355", "BYK-358N", "BYK-361N", "BYK-380", "BYK-381" and "BYK-392" (BYK Chemie).

[0079] Leveling agents containing a fluorine atom-containing compound as a main component include "Megafac (registered trademark) R-08", "R-30", "R-90", "F-410", "F-411", "F-443", "F-445", "F-470", "F-471", "F-477", "F-479", "F-482" and "F-483" (DIC Corporation); "Surflon (registered trademark) S-381" and "S-38 2”, “S-383”, “S-393”, “SC-101”, “SC-105”, “KH-40”, and “SA-100” (AGC Seimi Chemical Co., Ltd.); “E1830”, “E5844” (Daikin Fine Chemical Research Institute Ltd.); “F-TOP EF301”, “F-TOP EF303”, “F-TOP EF351”, and “F-TOP EF352” (Mitsubishi Materials Electronic Chemicals Co., Ltd.).

[0080] The content of the leveling agent in the polymerizable liquid crystal composition of the present invention is preferably 0.05 to 5 parts by mass, more preferably 0.05 to 3 parts by mass, based on 100 parts by mass of the polymerizable liquid crystal compound. When the content of the leveling agent is within the above range, the polymerizable liquid crystal compound is easily horizontally aligned, and unevenness is unlikely to occur, so that a smoother polarizing film tends to be obtained.

[0081] The polymerizable liquid crystal composition of the present invention may contain additives other than the polymerization initiator, the photosensitizer, and the leveling agent. Examples of the additives include a release agent, a stabilizer, a colorant such as a bluing agent, a flame retardant, and a lubricant. When the polymerizable liquid crystal composition contains other additives, the content of the other additives is preferably more than 0% and not more than 20% by mass, more preferably more than 0% and not more than 10% by mass, based on the solid content of the polymerizable liquid crystal composition.

[0082] The polymerizable liquid crystal composition of the present invention may contain a solvent. Generally, compounds exhibiting smectic liquid crystallinity have high viscosity, so that adding a solvent to the polymerizable liquid crystal composition facilitates coating, and as a result, in many cases, the formation of a polarizing film is facilitated. The solvent can be appropriately selected according to the solubility of the polymerizable liquid crystal compound and the dichroic dye, and examples of the solvent include alcohol solvents such as water, methanol, ethanol, ethylene glycol, isopropyl alcohol, propylene glycol, methyl cellosolve, butyl cellosolve, and propylene glycol monomethyl ether; ester solvents such as ethyl acetate, butyl acetate, ethylene glycol methyl ether acetate, γ-butyrolactone, propylene glycol methyl ether acetate, and ethyl lactate; ketone solvents such as acetone, methyl ethyl ketone, cyclopentanone, cyclohexanone, methyl amyl ketone, and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; aromatic hydrocarbon solvents such as toluene and xylene; nitrile solvents such as acetonitrile; ether solvents such as tetrahydrofuran and dimethoxyethane; and chlorinated hydrocarbon solvents such as chloroform and chlorobenzene. These solvents may be used alone or in combination of two or more. The content of the solvent is preferably 100 to 1900 parts by mass, more preferably 150 to 900 parts by mass, and further preferably 180 to 600 parts by mass, based on 100 parts by mass of the solid components constituting the polymerizable liquid crystal composition.

[0083] The polymerizable liquid crystal composition of the present invention can be prepared by generally mixing and stirring the polymerizable liquid crystal compound, the dichroic dye and the antioxidant, as well as the above-mentioned additives and solvent, etc., as required.

[0084] The polymerizable liquid crystal composition of the present invention has an excellent effect of suppressing photodegradation of a dichroic dye and can provide a polarizing film whose polarizing performance is unlikely to deteriorate over time, and therefore can be suitably used for producing a polarizing film.

[0085] A polarizing film having a high degree of alignment order can be produced using the polymerizable liquid crystal composition of the present invention. Polarizing films with a high degree of orientational order show Bragg peaks derived from higher-order structures such as hexatic and crystalline phases in X-ray diffraction measurements. The Bragg peak means a peak derived from the planar periodic structure of molecular orientation. Therefore, in a polarizing film formed from the polymerizable liquid crystal composition of the present invention, it is preferable that the polymerizable liquid crystal compound or its polymer is oriented so that the polarizing film shows a Bragg peak in X-ray diffraction measurement, and more preferably, the molecules of the polymerizable liquid crystal compound are oriented in the direction of absorbing light, that is, "horizontal orientation". In the present invention, a polarizing film in which the planar periodicity of the molecular orientation is 3.0 to 6.0 Å is preferable. A high degree of orientation order that shows a Bragg peak can be realized by controlling the type of polymerizable liquid crystal compound used, the type and amount of antioxidant, the type and amount of dichroic dye, etc.

[0086] As described above, by blending an antioxidant that satisfies formula (1) in relation to the polymerizable liquid crystal composition, a high inhibitory effect against photodegradation of the dichroic dye can be obtained while maintaining the high degree of orientational order of the polymerizable liquid crystal compound, and therefore a polarizing film that has excellent polarization performance and is unlikely to deteriorate over time can be obtained. Thus, the present invention provides a polarizing film that is a cured product of a polymerizable liquid crystal composition containing a dichroic dye, a polymerizable liquid crystal compound, and an antioxidant, the polarizing film exhibits a Bragg peak in X-ray diffraction measurement, and the antioxidant satisfies formula (1) in relation to the polymerizable liquid crystal compound: 0.8℃ ≦ T1-T2 (1) (In the formula, T1 is the phase transition temperature to the liquid crystal phase which appears at the lowest temperature side when the phase transition temperature of the polymerizable liquid crystal compound is measured while heating the compound in the air to 130° C. and then cooling to 23° C. at a rate of 5° C. / min, and T2 is the phase transition temperature to the liquid crystal phase which appears at the lowest temperature side when the phase transition temperature of a mixture of 100 parts by mass of the polymerizable liquid crystal compound and 1 part by mass of the antioxidant is measured while heating the compound in the air to 130° C. and then cooling to 23° C. at a rate of 5° C. / min.) This also applies to polarizing films that satisfy the above criteria.

[0087] In the polymerizable liquid crystal composition used to form the polarizing film of the present invention, the polymerizable liquid crystal compound, the dichroic dye, and the antioxidant may be the same as those exemplified above as the polymerizable liquid crystal compound, the dichroic dye, and the antioxidant contained in the polymerizable liquid crystal composition of the present invention. The polymerizable liquid crystal composition used to form the polarizing film of the present invention may contain a polymerization initiator, a leveling agent, other additives, a solvent, and the like. These components may be the same as those exemplified above as the components contained in the polymerizable liquid crystal composition of the present invention.

[0088] The polarizing film of the present invention can be produced, for example, by forming a coating film of the polymerizable liquid crystal composition of the present invention; removing the solvent from the coating; raising the temperature to a temperature at which the polymerizable liquid crystal compound undergoes a phase transition to a liquid phase or higher, and then lowering the temperature to cause the polymerizable liquid crystal compound to undergo a phase transition to a smectic phase (smectic liquid crystal state); and The polymerizable liquid crystal compound is polymerized while maintaining the smectic phase (smectic liquid crystal state). The composition can be produced by a method comprising the steps of:

[0089] The coating film of the polymerizable liquid crystal composition can be formed by applying the polymerizable liquid crystal composition, particularly a polymerizable liquid crystal composition whose viscosity has been adjusted by adding a solvent (hereinafter, also referred to as a "polarizing film-forming composition"), onto a substrate or an alignment film described later, etc. The polymerizable liquid crystal composition may be directly applied onto a retardation film or other layers constituting the polarizing plate of the present invention.

[0090] The substrate is usually a transparent substrate. When the substrate is not placed on the display surface of a display element, for example, when a laminate obtained by removing the substrate from a polarizing film is placed on the display surface of a display element, the substrate does not have to be transparent. The transparent substrate means a substrate having transparency capable of transmitting light, particularly visible light, and the transparency means a property in which the transmittance for light rays having a wavelength of 380 to 780 nm is 80% or more. Specific examples of transparent substrates include light-transmitting resin substrates. Examples of resins constituting the light-transmitting resin substrate include polyolefins such as polyethylene and polypropylene; cyclic olefin resins such as norbornene-based polymers; polyvinyl alcohol; polyethylene terephthalate; polymethacrylic acid esters; polyacrylic acid esters; cellulose esters such as triacetyl cellulose, diacetyl cellulose, and cellulose acetate propionate; polyethylene naphthalate; polycarbonate; polysulfone; polyether sulfone; polyether ketone; polyphenylene sulfide, polyphenylene oxide, and the like. From the viewpoint of availability and transparency, polyethylene terephthalate, polymethacrylic acid ester, cellulose ester, cyclic olefin resin, or polycarbonate is preferred. Cellulose ester is a material in which a part or all of the hydroxyl groups contained in cellulose are esterified, and is easily available on the market. Cellulose ester substrates are also easily available on the market. Commercially available cellulose ester substrates include "FUJITAC FILM" (Fuji Photo Film Co., Ltd.); "KC8UX2M", "KC8UY" and "KC4UY" (Konica Minolta Opto Co., Ltd.).

[0091] The properties required for the substrate vary depending on the configuration of the polarizing film, but generally, a substrate with as small a retardation as possible is preferred. Examples of substrates with as small a retardation as possible include cellulose ester films with no retardation, such as Zerotack (Konica Minolta Opto, Inc.) and Z-tack (Fujifilm Corporation). Unstretched cyclic olefin resin substrates are also preferred. The surface of the substrate on which the polarizing film is not laminated may be subjected to hard coat treatment, antireflection treatment, antistatic treatment, etc.

[0092] If the substrate is too thin, the strength decreases and the processability tends to be poor, so the thickness is usually 5 to 300 μm, preferably 20 to 200 μm, and more preferably 20 to 100 μm.

[0093] Examples of a method for applying the composition for forming a polarizing film to a substrate or the like include known methods such as application methods such as spin coating, extrusion, gravure coating, die coating, bar coating, and applicator methods, and printing methods such as flexography.

[0094] Next, the solvent is removed by drying or the like under conditions in which the polymerizable liquid crystal compound contained in the coating film obtained from the composition for forming a polarizing film does not polymerize, thereby forming a dried coating film. Examples of the drying method include natural drying, ventilation drying, heat drying, and reduced pressure drying.

[0095] Furthermore, in order to cause the polymerizable liquid crystal compound to undergo a phase transition to a liquid phase, the temperature is raised to a temperature at which the polymerizable liquid crystal compound undergoes a phase transition to a liquid phase or higher, and then the temperature is lowered to cause the polymerizable liquid crystal compound to undergo a phase transition to a smectic phase (smectic liquid crystal state). Such a phase transition may be performed after the solvent in the coating film is removed, or may be performed simultaneously with the removal of the solvent.

[0096] By polymerizing the polymerizable liquid crystal compound while maintaining the smectic liquid crystal state of the polymerizable liquid crystal compound, a cured film of the polymerizable liquid crystal composition is formed as a polarizing film. The polymerization method is preferably a photopolymerization method. In the photopolymerization, the light to be irradiated to the dried coating film is appropriately selected according to the type of photopolymerization initiator contained in the dried coating film, the type of polymerizable liquid crystal compound (particularly, the type of polymerizable group possessed by the polymerizable liquid crystal compound) and the amount thereof. Specific examples thereof include one or more types of light selected from the group consisting of visible light, ultraviolet light, infrared light, X-rays, α-rays, β-rays and γ-rays, and active electron beams. Among them, ultraviolet light is preferred in that the progress of the polymerization reaction is easily controlled and that photopolymerization devices widely used in this field can be used, and it is preferable to select the types of polymerizable liquid crystal compound and photopolymerization initiator contained in the polymerizable liquid crystal composition so that they can be photopolymerized by ultraviolet light. In addition, the polymerization temperature can also be controlled by irradiating light while cooling the dried coating film with an appropriate cooling means during polymerization. By adopting such a cooling means, the polymerization of the polymerizable liquid crystal compound can be carried out at a lower temperature, so that a polarizing film can be appropriately formed even if a substrate having a relatively low heat resistance is used. During photopolymerization, a patterned polarizing film can also be obtained by performing masking and development.

[0097] Examples of the light source of the active energy rays include a low-pressure mercury lamp, a medium-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a xenon lamp, a halogen lamp, a carbon arc lamp, a tungsten lamp, a gallium lamp, an excimer laser, an LED light source emitting light in the wavelength range of 380 to 440 nm, a chemical lamp, a black light lamp, a microwave-excited mercury lamp, and a metal halide lamp.

[0098] The UV irradiation intensity is usually 10 to 3,000 mW / cm 2The ultraviolet irradiation intensity is preferably an intensity in a wavelength region effective for activating a photopolymerization initiator. The time for light irradiation is usually 0.1 seconds to 10 minutes, preferably 1 second to 5 minutes, more preferably 5 seconds to 3 minutes, and further preferably 10 seconds to 1 minute. When irradiating once or multiple times with such ultraviolet irradiation intensity, the integrated light amount is 10 to 3,000 mJ / cm. 2 , preferably 50 to 2,000 mJ / cm 2 , more preferably 100 to 1,000 mJ / cm 2 It is.

[0099] By carrying out photopolymerization, the polymerizable liquid crystal compound is polymerized while maintaining the liquid crystal state of the smectic phase, preferably the high-order smectic phase, to form a polarizing film. The polarizing film obtained by polymerizing the polymerizable liquid crystal compound while maintaining the liquid crystal state of the smectic phase has an advantage of having a higher polarization performance due to the action of the dichroic dye, compared to conventional host-guest type polarizing films, i.e., polarizing films made of a liquid crystal state of a nematic phase. Furthermore, it has an advantage of having superior strength compared to films coated with only a dichroic dye or a lyotropic liquid crystal.

[0100] The thickness of the polarizing film can be appropriately selected depending on the display device to which it is applied, and is preferably 0.1 to 10 μm, more preferably 0.3 to 4 μm, and further preferably 0.5 to 3 μm.

[0101] The polarizing film is preferably formed on an alignment film. The alignment film has an alignment regulating force that aligns the polymerizable liquid crystal compound in a desired direction. The alignment film is preferably one that has solvent resistance that does not dissolve the composition containing the polymerizable liquid crystal compound by coating, etc., and has heat resistance in a heat treatment for removing the solvent or orienting the polymerizable liquid crystal compound. Examples of such alignment films include alignment films containing an orienting polymer, photo-alignment films, groove alignment films having a concave-convex pattern or a plurality of grooves on the surface, and stretched films stretched in the alignment direction. From the viewpoint of the accuracy and quality of the alignment angle, photo-alignment films are preferred.

[0102] Examples of the oriented polymer include polyamides and gelatins having an amide bond in the molecule, polyimides having an imide bond in the molecule, and polyamic acids, which are hydrolyzates thereof, polyvinyl alcohol, alkyl-modified polyvinyl alcohol, polyacrylamide, polyoxazole, polyethyleneimine, polystyrene, polyvinylpyrrolidone, polyacrylic acid, and polyacrylic acid esters. Among these, polyvinyl alcohol is preferred. The oriented polymers can be used alone or in combination of two or more kinds.

[0103] An alignment film containing an alignment polymer is usually obtained by applying a composition in which an alignment polymer is dissolved in a solvent (hereinafter, sometimes referred to as an "alignment polymer composition") to a substrate and removing the solvent, or by applying an alignment polymer composition to a substrate, removing the solvent, and rubbing (rubbing method). Examples of the solvent include the same solvents as those exemplified above as solvents that can be used when forming a polarizing film.

[0104] The concentration of the orienting polymer in the orienting polymer composition may be within a range in which the orienting polymer material can be completely dissolved in the solvent, and is preferably 0.1 to 20% in terms of solid content relative to the solution, and more preferably about 0.1 to 10%.

[0105] As the oriented polymer composition, a commercially available alignment film material may be used as it is. Examples of commercially available alignment film materials include Sunever (registered trademark, manufactured by Nissan Chemical Industries, Ltd.) and Optomer (registered trademark, manufactured by JSR Corporation).

[0106] The method for applying the orientable polymer composition to a substrate may be the same as those exemplified as the method for applying the composition for forming a polarizing film to a substrate.

[0107] Methods for removing the solvent contained in the orientable polymer composition include natural drying, ventilation drying, heat drying, and reduced pressure drying.

[0108] In order to impart an alignment control force to the alignment film, a rubbing treatment can be carried out as necessary (rubbing method).

[0109] An example of a method for imparting an orientation control force by a rubbing method is to bring an oriented polymer film formed on the surface of a substrate by applying an oriented polymer composition to the substrate and annealing the composition into contact with a rotating rubbing roll wrapped with a rubbing cloth.

[0110] A photo-alignment film is usually obtained by applying a composition containing a polymer or monomer having a photoreactive group and a solvent (hereinafter also referred to as a "photo-alignment film forming composition") to a substrate and irradiating the substrate with polarized light (preferably polarized UV). A photo-alignment film is more preferable in that the direction of the alignment control force can be arbitrarily controlled by selecting the polarization direction of the irradiated polarized light.

[0111] The photoreactive group refers to a group that generates liquid crystal alignment ability by irradiation with light. Specifically, it includes groups involved in photoreactions that induce molecular alignment or are the origin of liquid crystal alignment ability, such as isomerization reaction, dimerization reaction, photocrosslinking reaction, or photodecomposition reaction, caused by irradiation with light. Among them, groups involved in dimerization reaction or photocrosslinking reaction are preferred in terms of excellent alignment ability. As the photoreactive group, a group having an unsaturated bond, particularly a double bond, is preferred, and a group having at least one selected from the group consisting of a carbon-carbon double bond (C=C bond), a carbon-nitrogen double bond (C=N bond), a nitrogen-nitrogen double bond (N=N bond), and a carbon-oxygen double bond (C=O bond) is particularly preferred.

[0112] Examples of photoreactive groups having a C=C bond include vinyl groups, polyene groups, stilbene groups, stilbazolyl groups, stilbazolium groups, chalcone groups, and cinnamoyl groups. Examples of photoreactive groups having a C=N bond include groups having structures such as aromatic Schiff bases and aromatic hydrazones. Examples of photoreactive groups having an N=N bond include azobenzene groups, azonaphthalene groups, aromatic heterocyclic azo groups, bisazo groups, formazan groups, and groups having an azoxybenzene structure. Examples of photoreactive groups having a C=O bond include benzophenone groups, coumarin groups, anthraquinone groups, and maleimide groups. These groups may have substituents such as alkyl groups, alkoxy groups, aryl groups, allyloxy groups, cyano groups, alkoxycarbonyl groups, hydroxyl groups, sulfonic acid groups, and halogenated alkyl groups.

[0113] Among them, photoreactive groups involved in photodimerization are preferred, and cinnamoyl and chalcone groups are preferred because the amount of polarized light irradiation required for photoalignment is relatively small and a photoalignment film having excellent thermal stability and stability over time is easily obtained. As the polymer having a photoreactive group, one having a cinnamoyl group such that the terminal of the polymer side chain has a cinnamic acid structure is particularly preferred.

[0114] A photo-alignment-inducing layer can be formed on a substrate by applying the composition for forming a photo-alignment film on the substrate. The solvent contained in the composition can be the same as the solvents exemplified above as the solvents that can be used when forming a polarizing film, and can be appropriately selected depending on the solubility of the polymer or monomer having a photoreactive group.

[0115] The content of the polymer or monomer having a photoreactive group in the composition for forming a photo-alignment film can be appropriately adjusted depending on the type of polymer or monomer and the thickness of the intended photo-alignment film, but is preferably at least 0.2% by mass, more preferably in the range of 0.3 to 10% by mass, based on the mass of the composition for forming a photo-alignment film. The composition for forming a photo-alignment film may contain a polymer material such as polyvinyl alcohol or polyimide, or a photosensitizer, within a range that does not significantly impair the properties of the photo-alignment film.

[0116] The method of applying the composition for forming a photo-alignment film to a substrate may be the same as the method of applying the alignment composition to a substrate. The method of removing the solvent from the applied composition for forming a photo-alignment film may be natural drying, ventilation drying, heat drying, reduced pressure drying, etc.

[0117] The polarized light may be irradiated directly with polarized UV light after removing the solvent from the photo-alignment film-forming composition applied on the substrate, or may be irradiated with polarized light from the substrate side and then transmitted through the substrate. It is particularly preferable that the polarized light is substantially parallel light. The wavelength of the polarized light to be irradiated is preferably in a wavelength range in which the photoreactive group of the polymer or monomer having a photoreactive group can absorb light energy. Specifically, UV (ultraviolet light) having a wavelength of 250 to 400 nm is particularly preferable. Examples of light sources used for the polarized light irradiation include xenon lamps, high-pressure mercury lamps, ultra-high-pressure mercury lamps, metal halide lamps, and ultraviolet lasers such as KrF and ArF, and high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are more preferable. Among these, high-pressure mercury lamps, ultra-high-pressure mercury lamps, and metal halide lamps are preferable because they have a high emission intensity of ultraviolet light with a wavelength of 313 nm. The light from the light source can be irradiated through an appropriate polarizer to irradiate the polarized UV light. As such a polarizer, a polarizing filter, a polarizing prism such as a Glan-Thompson or Glan-Taylor type polarizer, or a wire grid type polarizer can be used.

[0118] If masking is performed during rubbing or polarized light irradiation, a plurality of regions (patterns) in which the liquid crystal alignment directions are different can be formed.

[0119] A groove alignment film is a film that has a concave-convex pattern or multiple grooves on the film surface. When a polymerizable liquid crystal compound is applied to a film with multiple equally spaced linear grooves, the liquid crystal molecules are aligned in the direction along the grooves.

[0120] Methods for obtaining a groove alignment film include a method in which the surface of a photosensitive polyimide film is exposed to light through an exposure mask having slits in a pattern shape, followed by development and rinsing to form an uneven pattern; a method in which a layer of uncured UV-curable resin is formed on a plate-shaped master having grooves on its surface, the formed resin layer is transferred to a substrate and then cured; and a method in which a roll-shaped master having multiple grooves is pressed against an uncured UV-curable resin film formed on a substrate to form unevenness, followed by curing.

[0121] The thickness of the alignment film (alignment film containing an alignment polymer or photoalignment film) is usually in the range of 10 to 10,000 nm, preferably in the range of 10 to 1000 nm, more preferably 500 nm or less, further preferably 10 to 200 nm, and particularly preferably 50 to 150 nm.

[0122] The present invention includes a polarizing plate (elliptical polarizing plate) comprising the polarizing film of the present invention and a retardation film. In the polarizing plate of the present invention, the retardation film is represented by the formula (X): 100 ≦ Re(550) ≦ 180 (X) (wherein Re(550) represents an in-plane retardation value at a wavelength of 550 nm) It is preferable that the following is satisfied. When the retardation film has an in-plane retardation value represented by the above (X), it functions as a so-called λ / 4 plate. The above formula (X) is preferably 100 nm≦Re(550)≦180 nm, and more preferably 120 nm≦Re(550)≦160 nm. Note that Re(550) can be measured by the method described in the Examples.

[0123] In the polarizing plate of the present invention, the angle between the slow axis of the retardation film and the absorption axis of the polarizing film is preferably substantially 45°. In the present invention, "substantially 45°" means 45°±5°.

[0124] Furthermore, the retardation film has the formula (Y): Re(450) / Re(550) < 1 (Y) (wherein Re(450) and Re(550) represent in-plane retardation values ​​at wavelengths of 450 nm and 550 nm, respectively). It is preferable that the above formula (Y) is satisfied. The retardation film satisfying the above formula (Y) has a so-called reverse wavelength dispersion and shows excellent polarization performance. The value of Re(450) / Re(550) is preferably 0.93 or less, more preferably 0.88 or less, even more preferably 0.86 or less, preferably 0.80 or more, more preferably 0.82 or more.

[0125] The retardation film may be a stretched film that gives retardation by stretching a polymer, but from the viewpoint of thinning the polarizing plate, it is preferable that the retardation film is a cured product of a polymerizable liquid crystal composition (hereinafter also referred to as "polymerizable liquid crystal composition (B)") containing a polymerizable liquid crystal compound, and is composed of a polymer in an oriented state of the polymerizable liquid crystal compound. The polymerizable liquid crystal compound (hereinafter also referred to as "polymerizable liquid crystal compound (B)") that forms the retardation film means a liquid crystal compound having a polymerizable functional group, particularly a photopolymerizable functional group. The photopolymerizable functional group means a group that can participate in a polymerization reaction by an active radical or an acid generated from a photopolymerization initiator. Examples of the photopolymerizable functional group include a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among them, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferable, and an acryloyloxy group is more preferable. The polymerizable liquid crystal compound (B) may be a thermotropic liquid crystal or a lyotropic liquid crystal, and may be a nematic liquid crystal or a smectic liquid crystal as a phase ordered structure. As the polymerizable liquid crystal compound (B), only one type may be used, or two or more types may be used in combination.

[0126] As the polymerizable liquid crystal compound (B), from the viewpoints of easiness of film formation and imparting retardation represented by the above formula (Y), a compound satisfying all of the following (a) to (d) can be mentioned.

[0127] (A) A compound having thermotropic liquid crystallinity; (a) The polymerizable liquid crystal compound has π electrons in the long axis direction (a). (c) It has π electrons in a direction intersecting with the long axis direction (a) [intersecting direction (b)]. (D) The total number of π electrons present in the long axis direction (a) is N(πa), and the total number of molecular weights present in the long axis direction is N(Aa), where N(πa) is the total number of π electrons present in the long axis direction, and N(Aa) is the total number of molecular weights present in the long axis direction. The π electron density in the long axis direction (a) of a polymerizable liquid crystal compound is defined by the formula (i): D(πa)=N(πa) / N(Aa) (i) The total number of π electrons present in the cross direction (b) is N(πb), and the total number of molecular weights present in the cross direction (b) is N(Ab), where N(πb) is the total number of π electrons present in the cross direction (b), and the cross direction (b) is the π electron density of the polymerizable liquid crystal compound defined by formula (ii): D(πb)=N(πb) / N(Ab) (ii) But, 0≦[D(πa) / D(πb)]≦1 (i.e., the π electron density in the cross direction (b) is greater than the π electron density in the long axis direction (a).) The polymerizable liquid crystal compound (B) that satisfies all of the above (A) to (D) can form a nematic phase by coating on an alignment film formed by rubbing treatment and heating to a phase transition temperature or higher. In the nematic phase formed by alignment of this polymerizable liquid crystal compound (B), the long axis directions of the polymerizable liquid crystal compounds are usually aligned so as to be parallel to each other, and these long axis directions become the alignment direction of the nematic phase.

[0128] The polymerizable liquid crystal compound (B) having the above characteristics generally exhibits reverse wavelength dispersion. Examples of the compound satisfying the above characteristics (a) to (d) include a compound represented by the formula (II): [ka] The compounds represented by formula (II) can be used alone or in combination of two or more kinds.

[0129] In formula (II), Ar represents a divalent aromatic group which may have a substituent. The aromatic group here refers to a group having a planar cyclic structure, and the number of π electrons of the cyclic structure is [4n+2] according to the Huckel rule. Here, n represents an integer. When a ring structure is formed by including heteroatoms such as -N= or -S-, the non-covalent bond electron pairs on these heteroatoms also satisfy the Huckel rule and have aromaticity. The divalent aromatic group preferably includes at least one of a nitrogen atom, an oxygen atom, and a sulfur atom.

[0130] G 1 and G2 each independently represents a divalent aromatic group or a divalent alicyclic hydrocarbon group, wherein a hydrogen atom contained in the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with a halogen atom, an alkyl group having 1 to 4 carbon atoms, a fluoroalkyl group having 1 to 4 carbon atoms, an alkoxy group having 1 to 4 carbon atoms, a cyano group, or a nitro group, and a carbon atom constituting the divalent aromatic group or the divalent alicyclic hydrocarbon group may be substituted with an oxygen atom, a sulfur atom, or a nitrogen atom.

[0131] L 1 , L 2 , B 1 and B. 2 each independently represents a single bond or a divalent linking group.

[0132] k and l each independently represent an integer of 0 to 3, and satisfy the relationship of 1≦k+l. Here, when 2≦k+l, B 1 and B. 2 , G 1 and G 2 may be the same as or different from each other.

[0133] E 1 and E 2 each independently represents an alkanediyl group having 1 to 17 carbon atoms, in which a hydrogen atom contained in the alkanediyl group may be substituted with a halogen atom, and -CH2- contained in the alkanediyl group may be substituted with -O-, -S- or -Si-. 1 and P 2 each independently represents a polymerizable group or a hydrogen atom, and at least one of them is a polymerizable group.

[0134] G 1 and G 2are each independently preferably a 1,4-phenylenediyl group which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, or a 1,4-cyclohexanediyl group which may be substituted with at least one substituent selected from the group consisting of halogen atoms and alkyl groups having 1 to 4 carbon atoms, more preferably a 1,4-phenylenediyl group substituted with a methyl group, an unsubstituted 1,4-phenylenediyl group, or an unsubstituted 1,4-trans-cyclohexanediyl group, and particularly preferably an unsubstituted 1,4-phenylenediyl group or an unsubstituted 1,4-trans-cyclohexanediyl group. 1 and G 2 At least one of L is preferably a divalent alicyclic hydrocarbon group. 1 or L 2 G binds to 1 and G 2 It is more preferable that at least one of the groups is a divalent alicyclic hydrocarbon group.

[0135] L 1 and L 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a1 OR a2 -, -R a3 COOR a4 -, -R a5 O.C.O.R. a6 -, R a7 OC=OOR a8 -, -N=N-, -CR c =CR d -, or -C≡C-, where R a1 ~R a8 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms; R c and R d represents an alkyl group having 1 to 4 carbon atoms or a hydrogen atom. 1 and L 2 are each independently preferably a single bond, -OR a2-1 -, -CH2-, -CH2CH2-, -COOR a4-1 -OR-a6-1 -, where R a2-1 , R a4-1 , R a6-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. 1 and L 2 are each independently more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, or -OCO-.

[0136] In a preferred embodiment of the present invention, G in formula (II) 1 and G 2 At least one of the divalent alicyclic hydrocarbon group is a divalent aromatic group Ar which may have a substituent and L which is -COO-. 1 and / or L 2 A polymerizable liquid crystal compound bonded by the formula:

[0137] B 1 and B. 2 are each independently preferably a single bond, an alkylene group having 1 to 4 carbon atoms, -O-, -S-, -R a9 OR a10 -, -R a11 COOR a12 -, -R a13 O.C.O.R. a14 - or R a15 OC=OOR a16 -, where R a9 ~R a16 each independently represents a single bond or an alkylene group having 1 to 4 carbon atoms. 1 and B. 2 are each independently preferably a single bond, -OR a10-1 -, -CH2-, -CH2CH2-, -COOR a12-1 -OR- a14-1 -, where R a10-1 , R a12-1 , R a14-1 Each independently represents a single bond, -CH2-, or -CH2CH2-. B 1 and B. 2are each independently more preferably a single bond, -O-, -CH2CH2-, -COO-, -COOCH2CH2-, -OCO-, or -OCOCH2CH2-.

[0138] From the viewpoint of expressing reverse wavelength dispersion, k and l are preferably in the range of 2≦k+l≦6, preferably k+l=4, and more preferably k=2 and l=2. When k=2 and l=2, a symmetrical structure is obtained, which is even more preferable.

[0139] E 1 and E 2 are each independently preferably an alkanediyl group having 1 to 17 carbon atoms, and more preferably an alkanediyl group having 4 to 12 carbon atoms.

[0140] P 1 or P 2 Examples of the polymerizable group represented by the formula (I) include an epoxy group, a vinyl group, a vinyloxy group, a 1-chlorovinyl group, an isopropenyl group, a 4-vinylphenyl group, an acryloyloxy group, a methacryloyloxy group, an oxiranyl group, and an oxetanyl group. Among these, an acryloyloxy group, a methacryloyloxy group, a vinyloxy group, an oxiranyl group, and an oxetanyl group are preferred, and an acryloyloxy group is more preferred.

[0141] It is preferable that Ar has at least one selected from an aromatic hydrocarbon ring which may have a substituent, an aromatic heterocycle which may have a substituent, and an electron-withdrawing group. Examples of the aromatic hydrocarbon ring include a benzene ring, a naphthalene ring, and an anthracene ring, and the like, and the benzene ring and the naphthalene ring are preferable. Examples of the aromatic heterocycle include a furan ring, a benzofuran ring, a pyrrole ring, an indole ring, a thiophene ring, a benzothiophene ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, a triazole ring, a triazine ring, a pyrroline ring, an imidazole ring, a pyrazole ring, a thiazole ring, a benzothiazole ring, a thienothiazole ring, an oxazole ring, a benzoxazole ring, and a phenanthroline ring. Among these, it is preferable that Ar has a thiazole ring, a benzothiazole ring, or a benzofuran ring, and it is more preferable that Ar has a benzothiazole group. When Ar contains a nitrogen atom, it is preferable that the nitrogen atom has π electrons.

[0142] In formula (II), the total number of π electrons contained in the divalent aromatic group represented by Ar is N π is preferably 8 or more, more preferably 10 or more, even more preferably 14 or more, and particularly preferably 16 or more. It is preferably 30 or less, more preferably 26 or less, and even more preferably 24 or less.

[0143] Examples of the aromatic group represented by Ar include groups of the formulae (Ar-1) to (Ar-23).

[0144] [ka]

[0145] In formulae (Ar-1) to (Ar-23), * represents a linking portion, Z 0 , Z 1 and Z 2each independently represents a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, an alkylsulfinyl group having 1 to 12 carbon atoms, an alkylsulfonyl group having 1 to 12 carbon atoms, a carboxyl group, a fluoroalkyl group having 1 to 12 carbon atoms, an alkoxy group having 1 to 6 carbon atoms, an alkylthio group having 1 to 12 carbon atoms, an N-alkylamino group having 1 to 12 carbon atoms, an N,N-dialkylamino group having 2 to 12 carbon atoms, an N-alkylsulfamoyl group having 1 to 12 carbon atoms, or an N,N-dialkylsulfamoyl group having 2 to 12 carbon atoms.

[0146] Q 1 and Q 2 are each independently -CR 2’ R 3’ -, -S-, -NH-, -NR 2’ -, -CO- or -O-; R 2’ and R 3’ each independently represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms.

[0147] J 1 and J. 2 each independently represents a carbon atom or a nitrogen atom.

[0148] Y 1 , Y 2 and Y 3 each independently represents an optionally substituted aromatic hydrocarbon group or an optionally substituted aromatic heterocyclic group.

[0149] W 1 and W 2 each independently represents a hydrogen atom, a cyano group, a methyl group or a halogen atom; and m represents an integer of 0 to 6.

[0150] Y 1 , Y 2 and Y 3Examples of the aromatic hydrocarbon group in the formula (I) include aromatic hydrocarbon groups having 6 to 20 carbon atoms, such as a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, and a biphenyl group. Examples of the aromatic hydrocarbon group include a phenyl group, a naphthyl group, an anthryl group, a phenanthryl group, and a biphenyl group, with a phenyl group and a naphthyl group being preferred, and a phenyl group being more preferred. Examples of the aromatic heterocyclic group include aromatic heterocyclic groups having 4 to 20 carbon atoms and containing at least one heteroatom such as a nitrogen atom, an oxygen atom, a sulfur atom, etc. Examples of the aromatic heterocyclic group include a furyl group, a pyrrolyl group, a thienyl group, a pyridinyl group, a thiazolyl group, a benzothiazolyl group, etc., and the furyl group, thienyl group, pyridinyl group, thiazolyl group, and benzothiazolyl group are preferred.

[0151] Y 1 and Y 2 may each independently be an optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group. The polycyclic aromatic hydrocarbon group refers to a condensed polycyclic aromatic hydrocarbon group or a group derived from an aromatic ring assembly. The polycyclic aromatic heterocyclic group refers to a condensed polycyclic aromatic heterocyclic group or a group derived from an aromatic ring assembly.

[0152] Z 0 , Z 1 and Z 2 are each preferably independently a hydrogen atom, a halogen atom, an alkyl group having 1 to 12 carbon atoms, a cyano group, a nitro group, or an alkoxy group having 1 to 12 carbon atoms; Z 0 More preferably, Z is a hydrogen atom, an alkyl group having 1 to 12 carbon atoms, or a cyano group. 1 and Z 2 is more preferably a hydrogen atom, a fluorine atom, a chlorine atom, a methyl group, or a cyano group.

[0153] Q 1 and Q 2 Examples include -NH-, -S-, and -NR 2’ - and -O- are preferred, R 2’ is preferably a hydrogen atom. 1 and Q 2As the group, -S-, -O- and -NH- are particularly preferable.

[0154] Among the formulae (Ar-1) to (Ar-23), the formulae (Ar-6) and (Ar-7) are preferred from the viewpoint of molecular stability.

[0155] In formulas (Ar-17) to (Ar-23), Y 1 is the nitrogen atom to which it is bonded and Z 0 may together form an aromatic heterocyclic group. Examples of the aromatic heterocyclic group include those mentioned above as aromatic heterocyclic rings that may be possessed by Ar. Examples include a pyrrole ring, an imidazole ring, a pyrroline ring, a pyridine ring, a pyrazine ring, a pyrimidine ring, an indole ring, a quinoline ring, an isoquinoline ring, a purine ring, and a pyrrolidine ring. The aromatic heterocyclic group may have a substituent. Y 1 is the nitrogen atom to which it is bonded and Z 0 In addition, it may be the above-mentioned optionally substituted polycyclic aromatic hydrocarbon group or polycyclic aromatic heterocyclic group. Examples of the polycyclic aromatic heterocyclic group include a benzofuran ring, a benzothiazole ring, and a benzoxazole ring. The compound represented by the formula (II) can be produced, for example, according to the method described in JP-A-2010-31223.

[0156] The content of the polymerizable liquid crystal compound (B) in the polymerizable liquid crystal composition (B) is, for example, 70 to 99.5 parts by mass, preferably 80 to 99 parts by mass, and more preferably 90 to 98 parts by mass, based on 100 parts by mass of the solid content of the polymerizable liquid crystal composition (B). When the content is within the above range, the orientation of the retardation film tends to be high. Here, the solid content refers to the total amount of components excluding volatile components such as the solvent from the polymerizable liquid crystal composition (B).

[0157] The polymerizable liquid crystal composition (B) may contain a polymerization initiator for initiating a polymerization reaction of the polymerizable liquid crystal compound (B). The polymerization initiator may be the same as those exemplified above as the polymerization initiator usable in the polymerizable liquid crystal composition (A). The polymerizable liquid crystal composition (B) may contain, as necessary, a photosensitizer, a leveling agent, and the additives exemplified as the additives contained in the polymerizable liquid crystal composition (A). The photosensitizer and the leveling agent may be the same as those exemplified above as the additives contained in the polymerizable liquid crystal composition (A).

[0158] The retardation film can be obtained by adding a solvent to the polymerizable liquid crystal composition (B) containing the polymerizable liquid crystal compound (B) and, if necessary, a polymerization initiator, an additive, etc., and mixing and stirring the composition (hereinafter, also referred to as a "composition for forming a retardation film") on a substrate or an alignment film, removing the solvent by drying, and curing the polymerizable liquid crystal compound (B) in the resulting coating film by heating and / or active energy rays. Examples of the substrate and / or alignment film used in the preparation of the retardation film include the same ones as those exemplified above as those usable in preparing the polarizing film of the present invention.

[0159] The solvent used in the composition for forming a retardation film, the method for applying the composition for forming a retardation film, the conditions for curing with active energy rays, and the like are all the same as those that can be used in the method for producing the polarizing film of the present invention.

[0160] The thickness of the retardation film can be appropriately selected depending on the display device to which it is applied. From the viewpoints of thinning and flexibility, the thickness is preferably 0.1 to 10 μm, more preferably 1 to 5 μm, and further preferably 1 to 3 μm.

[0161] The polarizing plate of the present invention comprises the polarizing film and the retardation film of the present invention, and preferably comprises a substrate, an alignment film (particularly a photoalignment film), the polarizing film and the retardation film of the present invention. The polarizing plate of the present invention may further comprise layers other than these (protective layer, adhesive layer, etc.). In the polarizing plate of the present invention, the polarizing film and the retardation film of the present invention may be bonded together via an adhesive layer or a pressure-sensitive adhesive layer. In the polarizing plate of the present invention, the retardation film may be formed directly on the polarizing film of the present invention by directly applying a composition for forming a retardation film to the polarizing film of the present invention.

[0162] The thickness of the polarizing plate of the present invention is preferably from 10 to 300 μm, more preferably from 20 to 200 μm, and further preferably from 25 to 100 μm, from the viewpoints of flexibility and visibility of the display device.

[0163] The present invention includes a display device comprising the polarizing film of the present invention or the polarizing plate of the present invention. The display device of the present invention can be obtained, for example, by attaching the polarizing film or polarizing plate of the present invention to the surface of a display device via a pressure-sensitive adhesive layer. The display device is a device having a display mechanism, and includes a light-emitting element or a light-emitting device as a light-emitting source. Examples of the display device include a liquid crystal display device, an organic electroluminescence (EL) display device, an inorganic electroluminescence (EL) display device, a touch panel display device, an electron emission display device (field emission display device (FED, etc.), surface field emission display device (SED)), electronic paper (display device using electronic ink or electrophoretic element), a plasma display device, a projection type display device (grating light valve (GLV) display device, display device having digital micromirror device (DMD), etc.), and a piezoelectric ceramic display. The liquid crystal display device includes any of a transmissive liquid crystal display device, a semi-transmissive liquid crystal display device, a reflective liquid crystal display device, a direct-view liquid crystal display device, and a projection type liquid crystal display device. These display devices may be display devices that display two-dimensional images, or may be stereoscopic display devices that display three-dimensional images. In particular, the display device of the present invention is preferably an organic EL display device or a touch panel display device, and more preferably an organic EL display device. EXAMPLES

[0164] <Preparation of polymerizable liquid crystal composition (hereinafter, also referred to as "polarizing film-forming composition")> The following components were mixed and stirred at 80° C. for 1 hour to obtain a polarizing film-forming composition (1). The azo dye described in the examples of JP 2013-101328 A was used as the dichroic dye. In the following examples, "%" and "parts" refer to % by mass and parts by mass, respectively, unless otherwise specified. ·Polymerizable liquid crystal compound: [ka] (A-6) 90 copies [ka] (A-7) 10 copies Dichroic dyes: Azo dyes; [ka] (Dichroic dye A) 2.5 parts [ka] (Dichroic dye B) 2.5 parts [ka] (Dichroic dye C) 2.5 parts Polymerization initiator: 2-Dimethylamino-2-benzyl-1-(4-morpholinophenyl)butan-1-one (Irgacure 369; manufactured by Chiba Specialty Chemicals Co., Ltd.) 6 parts Leveling agent: Polyacrylate compound (BYK-361N; manufactured by BYK-Chemie) 1.2 parts ·solvent: o-xylene 400 parts

[0165] Furthermore, compositions (2) to (18) for forming a polarizing film were obtained in the same manner as in the preparation of the composition (1) for forming a polarizing film, except that the compounds shown below were mixed as antioxidants in the amounts shown in Table 1 into the composition (1) for forming a polarizing film. The amount of antioxidant added in Table 1 indicates the amount relative to 100 parts by mass of the polymerizable liquid crystal compound in the composition for forming a polarizing film.

[0166] <Structure of antioxidant> The structures of the antioxidants used in the examples and comparative examples are as follows: [ka] (Antioxidant A: 4-n-octyloxyphenol) [ka] (Antioxidant B: 4,4'-biphenol) [ka] (Antioxidant C: 4-ethoxy-4'-hydroxybiphenyl) [ka] (Antioxidant D: 4-butoxy-4'-hydroxybiphenyl) [ka] (Antioxidant E: 4-octyloxy-4'-hydroxybiphenyl) [ka] (Antioxidant F: Dibutylhydroxytoluene) [ka] (Antioxidant G: Tinuvin 770; manufactured by BASF) [ka] (Antioxidant H: Sumilizer GP; manufactured by Sumitomo Chemical Co., Ltd.) [ka] (Antioxidant I: p-Methoxyphenol)

[0167] [Table 1]

[0168] <Measurement of liquid crystal phase transition temperature change T1-T2> (1) Formation of alignment film A 2% by weight aqueous solution of polyvinyl alcohol (polyvinyl alcohol 1000 fully saponified type, manufactured by Wako Pure Chemical Industries, Ltd.) was applied onto a glass substrate by spin coating, and after drying, a film with a thickness of 100 nm was formed. Subsequently, an alignment film was formed by subjecting the surface of the obtained film to a rubbing treatment. The rubbing treatment was performed using a semi-automatic rubbing device (product name: LQ-008 type, manufactured by Joyo Engineering Co., Ltd.) with a cloth (product name: YA-20-RW, manufactured by Yoshikawa Kako Co., Ltd.) under the conditions of a pressing amount of 0.15 mm, a rotation speed of 500 rpm, and 16.7 mm / s.

[0169] (2) Measurement of T1 As the polymerizable liquid crystal compound, 90 parts of the compound represented by formula (A-6), 10 parts of the compound represented by formula (A-7), and 400 parts of o-xylene were stirred at 80°C for 1 hour to obtain a homogeneously mixed composition. The obtained mixed composition was applied by spin coating onto the glass with the alignment film, and the solvent o-xylene was removed by heating and drying on a hot plate at 130°C for 3 minutes. The obtained coating film was then quickly cooled to room temperature to obtain a dried film of the polymerizable liquid crystal compound. The dried film was again heated to 130°C on a hot plate, and then cooled to 23°C at a rate of 5°C / min. The phase transition temperature was measured by observing with a polarizing microscope. As a result, it was confirmed that the phase transition occurred to a nematic liquid crystal phase at 113.7°C, the phase transition occurred to a smectic A phase at 109.6°C, the phase transition occurred to a smectic B phase at 92.0°C, and the smectic B phase was maintained until the temperature reached 23°C. Since the liquid crystal phase that appeared at the lowest temperature side in the above process was the smectic B phase, T1 was defined as 92.0°C, which is the phase transition temperature to the smectic B phase.

[0170] (3) Measurement of T2 A dried coating consisting of a mixture of an antioxidant and a polymerizable liquid crystal compound was obtained by the same method as that for measuring T1 in (2) above, except that 1 part by mass of antioxidants A to I was added to the above mixed composition relative to 100 parts by mass of the polymerizable liquid crystal compound. As a result of measuring the phase transition temperature by the same method as that for measuring T1 in (2) above, the liquid crystal phase appearing at the lowest temperature side in all mixtures was a smectic B phase. The phase transition temperatures (T2) to the liquid crystal phase appearing at the lowest temperature side when each antioxidant was contained are shown in Table 2.

[0171] [Table 2]

[0172] Example 1 (1) Preparation of photo-alignment film on substrate (i) Preparation of composition for forming photo-alignment film The following components described in JP 2013-033249 A were mixed, and the resulting mixture was stirred at 80° C. for 1 hour to obtain a composition for forming a photoalignment film. Photo-aligned polymers: [ka] 2nd part ·solvent: o-Xylene 98 parts

[0173] (ii) Formation of photo-alignment film A triacetyl cellulose film (KC8UX2M, manufactured by Konica Minolta, Inc.) was used as the substrate, and the film surface was subjected to a corona treatment, after which the composition for forming a photo-alignment film was applied and dried at 120°C to obtain a dry film. Polarized UV was irradiated onto this dry film to form a photo-alignment film, and a film with a photo-alignment film was obtained. The polarized UV treatment was carried out using a UV irradiation device (SPOT CURE SP-7, manufactured by Ushio Inc.) under conditions where the intensity measured at a wavelength of 365 nm was 100 mJ.

[0174] (2) Preparation of polarizing film The composition for forming a polarizing film (2) was applied onto the film with the photoalignment film obtained as described above by a bar coating method (#9 30 mm / s), and the polymerizable liquid crystal compound was subjected to phase transition to a liquid phase by heating and drying in a drying oven at 120°C for 1 minute, and then cooled to room temperature to cause the polymerizable liquid crystal compound to undergo phase transition to a smectic liquid crystal state. Next, a UV irradiation device (SPOT CURE SP-7; manufactured by Ushio Inc.) was used to expose the polymerizable liquid crystal compound to a smectic liquid crystal state at an exposure dose of 1000 mJ / cm. 2 By irradiating the layer formed from the composition for forming a polarizing film with ultraviolet light of 365 nm (based on 365 nm), the polymerizable liquid crystal compound contained in the dried film was polymerized while maintaining the smectic liquid crystal state of the polymerizable liquid crystal compound, and a polarizing film was formed from the dried film. The thickness of the polarizing film at this time was measured with a laser microscope (OLS3000 manufactured by Olympus Corporation) and found to be 2.3 μm. The polarizer thus obtained was a polarizing film and a substrate. X-ray diffraction measurements were also performed on this polarizing film using an X-ray diffractometer X'Pert PRO MPD (Spectris, Inc.). The results showed a sharp diffraction peak (Bragg peak) with a peak full width at half maximum (FWHM) of approximately 0.17° at 2θ = 20.2°. Similar results were also obtained with the incidence perpendicular to the rubbing. The order period (d) calculated from the peak position was approximately 4.4 Å, confirming the formation of a structure reflecting a high-order smectic phase.

[0175] (3) Preparation of polarizing film laminate Further, the polarizing film surface of the polarizer obtained above was subjected to a corona treatment, and then an aqueous solution (viscosity: 92 cP) containing 7 parts of carboxyl group-modified polyvinyl alcohol (Kuraray Poval KL318, Kuraray Co., Ltd.) and 3.5 parts of a water-soluble polyamide epoxy resin (Sumirez Resin 650, Sumika Chemtex Co., Ltd., aqueous solution with a solid content of 30% by mass) as a thermal crosslinking agent was applied to the corona-treated surface with a wire bar coater (#30). The aqueous solution was dried at 80°C for 5 minutes to form a protective layer, thereby producing a polarizer with a protective layer. Furthermore, glass (Corning, EagleXG) was attached to the protective layer via an adhesive layer formed of a pressure-sensitive adhesive (Lintec Co., Ltd., film thickness 25 μm) to obtain a polarizing film laminate of Example 1.

[0176] <Measurement of polarization degree Py and single unit transmittance Ty> The polarization degree Py and single transmittance Ty of the polarizing film laminate of Example 1 were measured as follows. The transmittance (Ta) in the transmission axis direction and the transmittance (Tb) in the absorption axis direction in the wavelength range of 380 nm to 780 nm were measured by a double beam method using a spectrophotometer (Shimadzu Corporation UV-3150) equipped with a folder with a polarizer. A mesh that cuts the amount of light by 50% was placed on the reference side of the folder. Using the following formulas (Formula 1) and (Formula 2), the single transmittance and the degree of polarization at each wavelength were calculated, and then luminosity correction was performed using the 2-degree visual field (C light source) of JIS Z 8701 to calculate the luminosity-corrected single transmittance (Ty) and luminosity-corrected degree of polarization (Py). Single transmittance Ty(%)=(Ta+Tb) / 2 (Equation 1) Degree of polarization Py(%) = (Ta-Tb) / (Ta+Tb)×100 (Equation 2)

[0177] The polarizing film laminates of Examples 2 to 15, Comparative Example 1, Comparative Example 2, and Reference Example 1 were obtained in the same manner except that the polarizing film-forming composition (2) was replaced with each of the compositions (1) and (3) to (18) shown in Table 3.

[0178] <Evaluation of light resistance> The light resistance of the laminates of Examples 1 to 15, Comparative Example 1, Comparative Example 2, and Reference Example 1 was evaluated according to the following method. The results are shown in Table 3.

[0179] The polarizing film laminate was placed in a light resistance tester (Suntest XLS+; manufactured by ATLAS) with the triacetyl cellulose film surface facing up, and the accumulated light intensity was measured at 23070 KJ / m 2 After the light irradiation under the above conditions, the polarization degree Py and the single transmittance Ty of the laminate were measured again, and the rate of change before and after the light resistance test was calculated.

[0180] [Table 3]

[0181] It was confirmed that the polarizing films (Examples 1 to 15) prepared from the polarizing film-forming compositions 2 to 16, that is, the polymerizable liquid crystal composition of the present invention, had good light resistance.

[0182] Example 16 <Preparation of circular polarizing plate> A retardation film prepared according to Example 1 of JP2015-143786A was transferred via an adhesive layer formed from a pressure-sensitive adhesive (manufactured by Lintec Corporation, film thickness 25 μm) onto the protective layer of the polarizer with a protective layer obtained in the process of preparing the polarizing film laminate of Example 5. Next, an aluminum metal plate was attached via an adhesive layer formed from a pressure-sensitive adhesive (manufactured by Lintec Corporation, film thickness 25 μm) to obtain an elliptical polarizing plate.

[0183] <Measurement of reflection hue a*, b*> The reflection hue of the triacetyl cellulose film surface, which was the substrate of the obtained elliptically polarizing plate, was measured with a spectrophotometer (CM-3700d, manufactured by Konica Minolta, Inc.) in terms of chromaticity a* and b* in the L*a*b* (CIE) color system.

[0184] <Evaluation of light resistance> Next, the substrate, triacetyl cellulose film, was placed face up in a light resistance tester (Suntest XLS+; manufactured by ATLAS) and the accumulated light dose was 23070 KJ / m 2 After the light irradiation under the above conditions, the chromaticity a* and b* of the laminate were measured again, and the rate of change before and after the light resistance test was calculated. The results are shown in Table 4.

[0185] [Table 4]

[0186] It was confirmed that the elliptically polarizing plate provided with the polarizing film of the present invention has a small amount of change in chromaticity and good light resistance.

Claims

1. A polymerizable liquid crystal composition comprising a polymerizable liquid crystal compound having at least one polymerizable group and exhibiting smectic liquid crystal properties, a dichroic dye, and an antioxidant, The polymerizable group of the polymerizable liquid crystal compound is a radical polymerizable group, The antioxidant is represented by the formula (5): A 1 -L 1 -(A 2 -L 2 ) n -A 3 (5) [In the formula, n is 0, L 1 is a single bond; A 1 is expressed by the formula (2): [In formula (2), R 1 is —OH, and R to R 5 is -H. is a group represented by A 3 is expressed by the formula (8) or (9): [In formulas (8) and (9), R 10 , R 11 , R 13 and R 14 is --H, and R 12 is a branched or unbranched alkyl group having 1 to 12 carbon atoms, or a branched or unbranched alkoxy group having 1 to 12 carbon atoms. is a group represented by the formula: and The antioxidant satisfies the formula (1) in relation to the polymerizable liquid crystal compound: 0.8℃ ≦ T1-T2 (1) (In the formula, T1 is the phase transition temperature to the liquid crystal phase which appears at the lowest temperature side when the phase transition temperature of the polymerizable liquid crystal compound is measured while heating the compound to 130° C. in the air and then cooling to 23° C. at a rate of 5° C. / min, and T2 is the phase transition temperature to the liquid crystal phase which appears at the lowest temperature side when the phase transition temperature of a mixture of 100 parts by mass of the polymerizable liquid crystal compound and 1 part by mass of the antioxidant is measured while heating the compound to 130° C. in the air and then cooling to 23° C. at a rate of 5° C. / min.) The polymerizable liquid crystal composition satisfies the above requirements.

2. The polymerizable liquid crystal composition according to claim 1 , further comprising a solvent.

3. 3. The polymerizable liquid crystal composition according to claim 1, wherein the dichroic dye is an azo dye.

4. 4. The polymerizable liquid crystal composition according to claim 1, wherein the polymerizable group of the polymerizable liquid crystal compound is an acryloyloxy group.

5. 5. The polymerizable liquid crystal composition according to claim 1, further comprising 0.1 to 15 parts by mass of an antioxidant based on 100 parts by mass of the polymerizable liquid crystal compound.

6. A polarizing film which is a cured product of a polymerizable liquid crystal composition containing a dichroic dye, a polymerizable liquid crystal compound, and an antioxidant, The polarizing film exhibits a Bragg peak in an X-ray diffraction measurement, The antioxidant is represented by the formula (5): A 1 -L 1 -(A 2 -L 2 ) n -A 3 (5) [In the formula, n is 0, L 1 is a single bond; A 1 is expressed by the formula (2): [In formula (2), R 1 is —OH, and R to R 5 is -H. is a group represented by A 3 is expressed by the formula (8) or (9): [In formulas (8) and (9), R 10 , R 11 , R 13 and R 14 is --H, and R 12 is a branched or unbranched alkyl group having 1 to 12 carbon atoms, or a branched or unbranched alkoxy group having 1 to 12 carbon atoms. is a group represented by the formula: and The antioxidant satisfies the formula (1) in relation to the polymerizable liquid crystal compound: 0.8℃ ≦ T1-T2 (1) (In the formula, T1 is the phase transition temperature to the liquid crystal phase which appears at the lowest temperature side when the phase transition temperature of the polymerizable liquid crystal compound is measured while heating the compound to 130° C. in the air and then cooling to 23° C. at a rate of 5° C. / min, and T2 is the phase transition temperature to the liquid crystal phase which appears at the lowest temperature side when the phase transition temperature of a mixture of 100 parts by mass of the polymerizable liquid crystal compound and 1 part by mass of the antioxidant is measured while heating the compound to 130° C. in the air and then cooling to 23° C. at a rate of 5° C. / min.) Meet the polarizing film.

7. A polarizing plate comprising the polarizing film according to claim 6 and a retardation film.

8. The retardation film has the formula (X): 100≦Re(550)≦180 (X) (wherein Re(550) represents an in-plane retardation value at a wavelength of 550 nm) 8. The polarizing plate according to claim 7, wherein the angle between the slow axis of the retardation film and the absorption axis of the polarizing film is substantially 45°.

9. The retardation film has the formula (Y): Re(450) / Re(550) < 1 (Y) (In the formula, Re(450) and Re(550) represent in-plane retardation values ​​at wavelengths of 450 nm and 550 nm, respectively.) The polarizing plate according to claim 7 or 8, which satisfies the above.

10. 10. The polarizing plate according to claim 7, wherein the retardation film is composed of a polymer of a polymerizable liquid crystal compound in an oriented state.

11. A display device comprising the polarizing film according to claim 6 or the polarizing plate according to any one of claims 7 to 10.

12. forming a coating film of the polymerizable liquid crystal composition according to any one of claims 1 to 5; removing the solvent from the coating; raising the temperature to a temperature at which the polymerizable liquid crystal compound undergoes a phase transition to a liquid phase or higher, and then lowering the temperature to cause the polymerizable liquid crystal compound to undergo a phase transition to a smectic phase; and The polymerizable liquid crystal compound is polymerized while maintaining the smectic phase. A method for producing a polarizing film, comprising the steps of:

Citation Information

Patent Citations

  • Dichroic Guest-Host Polarizers Containing Oriented Polymer Films

    JP2007510946A

  • Polarizer and method for manufacturing the same

    JP2013037353A

  • Mesogenic stabilizers

    US20120003401A1

  • Mesogenic stabilizers

    WO2013022610A1

  • Polymerizable composition and optically anistropic body using same

    WO2018012579A1